Exploring factors that influence the practice of Open Science by early career health researchers: a mixed methods study - Zečević, Ksenija (HRB Open Res, 2021)
Background: There is a growing global movement towards open science and ensuring that health research is more transparent. It is vital that the researchers are adequately prepared for this research environment from early in their careers. However, limited research has been conducted on the barriers and enablers to practicing open science for early career researchers. This study aimed to explore the views, experiences and factors influencing open science practices amongst ECRs working in health research. Methods: Semi-structured individual interviews were conducted with a convenience sample of ECRs working in health research. Participants also completed surveys regarding the factors influencing open science practices. Thematic analysis was used to analyse the qualitative data and descriptive statistical analyses were used to analyse survey data. Results: 14 ECRs participated. Two main themes were identified from interview data; Valuing Open Science and Creating a Culture for Open Science. Within ‘Valuing Open Science’, participants spoke about the conceptualisation of open science to be open across the entire research cycle, and important for producing better and more impactful research for patients and the public. Within ‘Creating a Culture of Open Science’ participants spoke about a number of factors influencing their practice of open science. These included cultural and academic pressures, the positives and negatives of increased accountability and transparency, and the need for more training and supporting resources to facilitate open science practices. Conclusion: ECRs see the importance of open science for beneficially impacting patient and public health but many feel that they are not fully supported to practice open science. Resources and supports including education and training are needed, as are better incentives for open science activities. Crucially, tangible engagement from institutions, funders and researchers is needed to facilitate the development of an open science culture.